2020
DOI: 10.20524/aog.2020.0478
|View full text |Cite
|
Sign up to set email alerts
|

Association of liver cirrhosis severity with anemia: does it matter?

Abstract: Background The etiology of anemia in liver disease is diverse and often multifactorial. Anemia is more severe in advanced stages of liver cirrhosis and can be a predictor of the severity of liver disease. Methods In this cross-sectional observational study, we included 181 cirrhotic patients with anemia owing to liver cirrhosis and its complications. The population was divided into 2 groups based on the model for end-stage liver disease (MELD) score and the severity of anemia was assessed in the 2 groups. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Anemia is the most common complication of liver cirrhosis, and the etiology of anemia in liver disease is diverse and often multifactorial. 8 The common causes are acute and chronic blood loss due to upper gastrointestinal bleeding, malnutrition, hypersplenism secondary to portal hypertension, and impaired coagulation. 8 Contrast with the literature, in this case the patient never had bleeding history, including hematochezia, melena, hematemesis, and hemoptoe.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is the most common complication of liver cirrhosis, and the etiology of anemia in liver disease is diverse and often multifactorial. 8 The common causes are acute and chronic blood loss due to upper gastrointestinal bleeding, malnutrition, hypersplenism secondary to portal hypertension, and impaired coagulation. 8 Contrast with the literature, in this case the patient never had bleeding history, including hematochezia, melena, hematemesis, and hemoptoe.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that lower haemoglobin levels are associated with an increased risk of post-BL ulcer bleeding. Singh et al [25] found that haemoglobin levels decrease spontaneously with the increasing severity of liver disease. This may suggest that our case group had more severe liver cirrhosis and therefore more severe varices than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The associated anemia entirely resolved in half of our patients and improved in 87.5% of patients six to twelve months after OLT. Anemia is common in cirrhotic patients; however, it is usually complex, and may be influenced by several factors, including etiology of cirrhosis and degree of portal hypertension[ 29 , 30 ] . Portal hypertension and hypersplenism can be contributing factors to anemia in cirrhosis; however, the magnitude of the effect is unclear[ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%